O mundo digital: o homem e o computador, uma comunicação em desenvolvimento - Braga, Luiz Antonio Fernandes (1998)
Analize what is happening in the Arts field since the use of the personal computer has spread. We are especially concerned with the latest times, with the arrival of the Internet in Brazil and especially in the Fine Arts Scholl of the Federal University of Rio de Janeiro. For having passed from a local processor to a communication interface, the personal computer can no longer be seen as one more tool available to the artist, but has to be analyzed, in his context, as a door to another dimension, another space – the cyberspace – where new contacts and new experiences can be made. Artists have therefore changed their way of relating to computers, inserting them into their lives, adopting them as one more extension on behalf of their work. In the Computer Graphics Lab of the Fine Arts School of the Federal University of Rio de Janeiro, these changes in the basic computer function has brought notice able changes, not only in the man-machine relation, but also in the man-man relation, in the real as well as in the virtual space.